Inside Bluetooth low energy - Gupta, Naresh (Artech House mobile communications series., 2016)
This updated and expanded second edition of the Artech House bestseller, Inside Bluetooth Low Energy, presents the recent developments within the Bluetooth Core Specifications 4.1 and 4.2. This new edition explores both Internet of Things (IoT) and Bluetooth Low Energy (LE) in one single flow and demonstrates how this technology is very well suited for IoT implementations. The book covers all the advances within the new specifications including Bluetooth LE enhanced power efficiency, faster connections, and enhanced privacy and security. Developed for ultra-low power devices, such as heart rate monitors, thermometers, and sensors, Bluetooth LE is one of the latest, most exciting enhancements to Bluetooth technology. This cutting-edge book presents an easy-to-understand, broad-based explanation of Bluetooth LE, its building blocks and how they all come together. Packed with examples and practical scenarios, the book helps readers rapidly gain a clear, solid understanding of Bluetooth LE in order to work more effectively with its specification. This book explores the architecture of the Bluetooth LE stack and functionality of its layers and includes a broad view of the technology, identifies the various building blocks, and explains how they come together. Readers will also find discussions on Bluetooth basics, providing the background information needed to master Bluetooth LE.